Application of fuzzy logic for routing in communication networks - Vrublevsky, Anton; Lesovoy, Ivan (Видавництво Львівської політехніки, 2012)
To satisfy QoS requirements we should take into consideration routing metrics that affect directly to the QoS. We will consider three parameters: bandwidth, losses and delays. For transmitting multimedia services it is desired to design some controlling mechanisms for solving different problems in a network in case of packet delays, losses etc. Because of complex nature of controlling mechanisms it is desired to design fuzzy logic controller. As input parameters will be three routing metrics mentioned above, whereas as output parameter will be network efficiency. The aim is to obtain better values of network efficiency using different rules from Rule Editor and using appropriate defuzzification method.
Keywords: fuzzy logic; linguistic variables; mambership function; fuzzy logic controller; fuzzy rules; routing metrics